PENGARUH TEMPERATUR AUSTEMPERING TERHADAP SIFAT MEKANIK DAN STRUKTUR MIKRO BESI COR KELABU DENGAN NIKEL 10% UNTUK KOMPONEN BOILER PLTU - Widyansyah, Fikri; Mabruri, Efendi; Alfirano, Alfirano (Jurnal Rekayasa Mesin, 2023)
Effect of austempering temperature on microstructure and mechanical properties gray cast iron with 10%wt nickel for boiler combustion application has been studied. Cast iron with the JIS FCD 45 standard with a minimum tensile strength of 414 MPa and a hardness of 187 HB is commonly used for this application. To improve its mechanical properties such as strength and hardness, austempering heat treatment usually applied. Austempering was carried out at 250°C, 300°C, 350°C, 400°C, and 450°C for 1 hour, with the same austenization temperature of 850°C for 1 hour. The highest increase in hardness was found at the austempering temperature of 250°C. The hardness was 321.80 HB or 19.30% of the initial hardness of 259.70 HB. In terms of strength, the highest increase occurred at the austempering temperature of 250°C which was 257 MPa or 31.52% of the initial strength of 176 MPa.